The Great Lakes of the World (GLOW) : Food-Web, Health and Integrity - Hecky, R. E.; Munawar, M. (Ecovision world monograph series., 2016)
The Great Lakes of the World (GLOW) is a series of international symposia organized by the Aquatic Ecosystem Health and Management Society in order to promote interaction and communication between Great Lakes scientists and communities around the world. The purpose of GLOW is to establish a platform where understanding of structure, function, and performance of healthy and damaged ecosystems from integrated, multidisciplinary, and sustainable perspectives is promoted. This book includes papers originating in part from the first of many international symposia--Exploring the Great Lakes of the World: Food-Web Dynamics, Health and Integrity, held at Victoria Falls, Zimbabwe. The following is adapted from the editorial: "As scientists, we accept that we can never know everything at one time about large aquatic ecosystems, due to temporal and spatial measurement limitations. This uncertainty can be reduced through sharing our knowledge of large systems so that others can incorporate our results into analyses of their systems. To that end, this book is a remarkable achievement as it does accomplish global coverage of large and great lakes."